Socialization for Private Sector of Hotel and Restaurant on Post Disaster of Tsunami in Banten, 2018 - Admiral Musa Julius; Suci Dewi Anugrah; I Dewa Ketut Kerta Widana (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2019)
We did socialization for private sector of Hotels and Restaurants on post disaster of tsunami which hit the west coast of Banten province at December 22, 2018. This disaster claimed 296 lives, 675 injuries, and 3 missing people. BMKG formed socialization team on post disaster in aim to normally public condition, sharing the skill and knowledge, and explained the history of earthquake and tsunami disasters in Banten. It was strongly needed by impacted private sector, west part of Banten coastal zone need to be concerned in the future on planning, also developing resources of disaster prevention, mitigation, and preparedness.